Using IoT-based mobile application to build smart parking system - Attarbashi, Zainab; Thamodharan, Tharshaan; Abuzaraida, Mustafa Ali; Iftikhar, Saman; Alansari, Noof Abdulaziz; Basri, Atikah Balqis; Handayani, Dini Oktarina Dwi (IEEE, 2023)
The idea of using the current technologies to build more sustainable smart cities has gained great popularity. One of attractive fields is Internet of Things applications to control vehicle traffic and parking which reduce energy consumption in smart cities. This paper presents an android mobile application system that allows users to check the availability and location of parking spots by using their smartphones. Main tools used for this project are the Arduino UNO and mobile application running with Android. Sensors were used to sense if the spot is empty, and then send that info to the mobile application. As the empty place is discovered to be vacant it is distinguished utilizing ultrasonic sensors which report it further. The system would not help the user to book parking spot but would show the availability of parking spot to reduce the searching time. This Smart Parking System is a basic prototype which can be improved later for real system by connecting the system to a GPS-based application which will direct the user to the spot itself and it can further be improved by using artificial intelligence to highlight different spots to different users